Influence of heat treatment on the microstructure and mechanical properties of 6061 aluminum alloy - Luqman Nulhaqem, Abdul Aziz (2013)
The process of heat treatment is the method by which metals are heated and cooled in a series of specific operations that never allow the metal to reach the molten state. The purpose of the heat treatment is to cause desire changes in the metallurgical structure and thus in the properties of metal parts. The aim of this research is to study the influence of heat treatment and natural aging mechanism on the microstructure and mechanical properties of aluminum alloy 6061. The aluminum alloy 6061 sample heat treated using T4 method which is heat treated at 550°C, 575°C and 600°C and then naturally aged at ambient environment for 3 hours. After heat treated process, the effects were investigated in terms of microstructure using metallurgical analysis and mechanical properties by tensile tests and hardness test. Tensile tests show that the yield stress and UTS have high value when heat treated at 600°C where 103.28693 MPa and 195.246895 MPa meanwhile the Young modulus heat treated at 550°C have high value; 84417.95106 MPa. For heat treatment specimens, the high VHN is specimen’s heat treated at 600°C which have value 85.7 and the lower VHN value is specimen’s heat treated at 550°C with value 57.5. The heat treatment process result soft aluminum alloy 6061. Lastly for microstructure observation, different microstructure appear within different heat treatment temperature. From the data and result that already determined, it achieved the objectives and scope of this research.